Life cycle assessment of municipal solid waste management in Nottingham, England: Past and future perspectives. (1st April 2020) - Wang, Dan; He, Jun; Tang, Yu-Ting; Higgitt, David; Robinson, Darren
Abstract: Since the enforcement of the EU Landfill Directive, EU waste directives were successively enforced in EU member states to facilitate the establishment of sustainable MSW management. Various changes have been made in England to reduce the global impact of its MSW management, but the effectiveness of these changes on mitigating the global warming potential (GWP) from MSW management has never been investigated in detail. This study assessed the historical GWP of MSW management in Nottingham throughout the period from April 2001 to March 2017 through life cycle assessment (LCA). The LCA results indicate continuous reductions in greenhouse gas (GHG) emissions from MSW management during the study period due to improvements in waste collection, treatment and material recycling, as well as waste prevention. These improvements resulted in a net reduction of GHG emission from 1076.0 kg CO2 –eq./t of MSW (or 498.2 kg CO2 –eq./Ca) in 2001/02 to 211.3 kg CO2 –eq./t of MSW (or 76.3 kg CO2 –eq./Ca) in 2016/17. A further reduction to −142.3 kg CO2 –eq./t of MSW (or −40.2 kg CO2 –eq./Ca) could be achieved by separating food waste from incinerated waste, treating organic waste via anaerobic digestion and by pretreating incinerated waste in a material recovery facility. Highlights: GHG emissions from MSW management generally show a reduction trend. Waste prevention significantly contributed to mitigation of GWP. GHG emissions arising from the transport of material for recycling have increased. Separately collecting and treating food waste further reduces GHG emissions. Improving energy recovery efficiency in the city's EfW plant is recommended.